High temperatures behaviour of mortars with incorporation of phase change materials - Cunha, Sandra Raquel Leite (2014)
In a society increasingly concerned with sustainability and good construction practices, it becomes urgent to develop and study the behaviour of the materials when submitted to the unfavourable conditions. Mortars are extensively used in building. The mortars with incorporation of phase change materials (PCM) have the ability to regulate the temperature inside buildings, contributing to the thermal comfort and reduction the use of heating and cooling equipment, using only the energy supplied by the sun. Currently, it emerges the need to develop functional mortars that can contribute to the energy efficiency. However, it is important that they present a good behaviour when subjected to aggressive conditions, such as high temperatures. The main purpose of this study was the behaviour at high temperatures of mortars with PCM, based in different binders. The binders studied were aerial lime, hydraulic lime, gypsum and cement. For each type of binder, different mortars were developed with different content of PCM. The proportion of PCM studied was 0% and 40% of the mass of the sand. It was possible to observe that the exposure to high temperatures, generally leads to a decrease in the mechanical properties of the studied mortars.